Environmental Reviews and Case Studies: Assessing Archaeological Resources. (1st September 2016) - Moratto, Michael J.
Abstract : This article presents an overview of archaeological resources and methods in the context of environmental impact assessment (EIA). Archaeological best practices in the EIA process are summarized and examples of deficient work are provided so that readers—particularly those who are responsible for review and approval of environmental studies—will be able to judge the adequacy and professional quality of archaeological work performed for their clients or agencies.